HUBUNGAN ANTARA OBESITAS SENTRAL DENGAN ADIPONEKTIN PADA PASIEN GERITARI DENGAN PENYAKIT JANTUNG KORONER - Gotera, Wira; Suastika, Ketut; Santoso, Anwar; Kuswardhani, Tuty (journal of internal medicine; Vol. 7, No. 2 Mei 2006, 2012)
Obesity is rapidly becoming a global problem not only in developed countries but also in developing countries such as Indonesia. Visceral obesity (central obesity) is an importance risk for cardiovascular disease and recognition that adipose tissue can be regarded as a large endocrine organ that secreted inflammatory and anti inflammatory molecules (adiponectin). This study aims to know the correlation between central obesity and adiponectin in geriatric coronary heart disease (CHD) patients. This study was cross sectional analytic study of geriatric CHD at out and in patients in Sanglah hospital. Data are presented as group mean ± SD and analyzed by t-test, chi-square, and Pearson correlation with SPSS 12 software. Forty five patients (35 males and 10 females), 23 patient unstable angina pectoris, 14 patient acute myocardial infarction, and 8 patient stable angina pectoris were recruited and examined. There was high prevalence of central obesity 51.1% (23 patients). Mean of log adiponectin were significantly difference between central obese and non central obese (1.80 ± 0.61 vs 1.09 ± 0.41 with p). Central obesity increased risk of hypoadiponectinemia 5 times than non central obesity (p=0.011, CI 95% 1.4-17.8). Waist circumference has negative correlation with log plasma adiponectin (R=-0.663, p<0.001). There was high prevalence of central obesity in geriatric coronary heart disease patients. Central obesity increased risk of hypoadiponectinemia 5 times than non central obesity. Waist circumference has negative correlation with plasma adiponectin. Increased of waist circumference will decrease of adiponectin (cardioprotective protein) and will increase risk of acute coronary syndrome in geriatric patients.
Keywords: central obesity, adiponectin, geriatric, coronary heart disease